Surgical Repair of Complex Aortopulmonary Window: A Case Study - He,Jigang (2018)
Abstract Aortopulmonary septal defect, also known as the aortopulmonary window, is a rare congenital macrovascular malformation. This case involves a 9-year-old boy with aortopulmonary septal defect (type I combined with type IV). Before surgery, milrinone and alprostadil were used to counteract high lung pressure. Surgery was performed under cardiopulmonary bypass, following which the pulmonary pressure decreased. The aorta was cut, and the right pulmonary artery opening was connected with the main pulmonary artery septal defect using polyester patch. An internal tunnel was made, and the deformity correction was completed. The child exhibited normal postoperative recovery with no discomfort. A complex aortopulmonary window is a rare condition that can be treated successfully with appropriate preoperative and surgical management.